Identity, Reasonableness and Being One Among Others Dialogue, Community, Education - Splitter, Laurance Joseph (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book brings the tools and ideas of Anglo-American analytic philosophy to bear on how we think about issues of contemporary significance, in a way that is accessible to a broad audience. While acknowledging empirical findings within the social sciences, it takes on the prescriptive task of imagining a better world, in which being citizens in a democracy means actively engaging with others. We cling to tribal affiliations which incline us to look inward and spurn those whom we deem to be "other." And we observe the mind-numbing, herd-like impact of social (and other) media on our capacity - and that of our children - to distinguish truth and good sense from falsehood and nonsense. Such problems demand our attention as reasonable persons who both think for themselves, and deliberate in good faith with others with whom they may well disagree. The good news is that while reasonableness cannot be taken for granted, it can - indeed, it must - be nurtured and it must be taught. This book both articulates a conception of reasonableness and exemplifies a clear standard of reasonableness, with respect to the questions it raises and the author's responses to them. .
Introduction -- What identity really is and why it matters -- On being a person as one among others -- The moral implications of being one among others (I): Descriptive and prescriptive perspectives on personhood, and the normative ideal of reasonableness -- The moral implications of being one among others (II): Persons, groups, and the Principle of Personal Worth -- Narrative and personhood: A fraught relationship -- Democracy and education: Cultivating reasonableness. .
Keywords: Education-Philosophy.; Social sciences-Philosophy.; Educational sociology; Educational Philosophy; Social Philosophy; Sociology of Education